Development of hippocampal functional connectivity during childhood. Issue 1 (1st September 2016) - Blankenship, Sarah L.; Redcay, Elizabeth; Dougherty, Lea R.; Riggins, Tracy
Abstract: The hippocampus is a medial temporal lobe structure involved in memory, spatial navigation, and regulation of stress responses, making it a structure critical to daily functioning. However, little is known about the functional development of the hippocampus during childhood due to methodological challenges of acquiring neuroimaging data in young participants. This is a critical gap given evidence that hippocampally‐mediated behaviors (e.g., episodic memory) undergo rapid and important changes during childhood. To address this gap, the present investigation collected resting‐state fMRI scans in 97, 4‐ to 10‐year‐old children. Whole brain seed‐based analyses of anterior, posterior, and whole hippocampal connectivity were performed to identify regions demonstrating stable (i.e., age‐controlled) connectivity profiles as well as age‐related differences in connectivity. Results reveal that the hippocampus is a highly connected structure of the brain and that most of the major components of the adult network are evident during childhood, including both unique and overlapping connectivity between anterior and posterior regions. Despite widespread age‐controlled connectivity, the strength of hippocampal connectivity with regions of lateral temporal lobes and the anterior cingulate increased throughout the studied age range. These findings have implications for future investigations of the development of hippocampally‐mediated behaviors and methodological applications for the appropriateness of whole versus segmented hippocampal seeds in connectivity analyses. Hum Brain Mapp 38:182–201, 2017 . © 2016 Wiley Periodicals, Inc.